Education Game of Javanese Language for 2nd Grade of Elementary Schools - Irse Surya Bagaskara (Soegijapranata Catholic University, 2016)
Local language is the language that is often used to communicate in daily life, but in the case studies in the field are very different. Some kids are more frequently using Indonesian language to communicate with each other. And it makes kids dont understand about Java language lessons at school. Because of that we hope this game